Groundwater modelling for determination of optimum pumping rate at Kubang Kerian of Kelantan - Sulaiman, Norazlan (2014)
Kelantan is the only state of Malaysia where about 40% of water supply comes from groundwater. Population of Kelantan is increasing and economy is growing like other parts of Malaysia. The increased population and developing economy will certainly increase water demand. Groundwater has to play an important role to meet the growing demand in the state. Therefore, abstraction of groundwater should be managed properly to avoid overexploitation. For proper management of groundwater resources, it is required to simulate groundwater status under different pumping situations. The major objective of the present research is to simulate groundwater flow at Kubang Kerian located in Kota Bahru of Kelantan by using a three-dimensional groundwater simulation model in order to determine the optimum pumping rate. The groundwater in the study area is recharged by rainfall and nearby river system. Therefore, the impact of groundwater abstraction on the river system especially during dry season is also assessed. Finally, the groundwater flow pattern and flow budget are determined by simulating both steady state and transient conditions of groundwater flow. The study reveals that maximum 30 MLD of water can be withdrawn in the study area without any negative impact on groundwater resources and surrounding ecosystem